Resistência à corrosão dos aços CA24 e CA50 frente à ação dos cloretos - Carvalho, Leonardo Gomes de Sá e (2014)
Corrosion of reinforcement in concrete structures constitutes one of the most serious and costly problems to be solved in construction. Currently, a number of professionals are somehow mobilized in order to prevent, control and repair concrete structures subjected or with steel corrosion. This paper presents and discusses the main results of an experimental study aimed to verify the corrosion resistance of two different types of steel, CA24 and CA50. The CA24 steel was widely used in construction of the 1930s to 1960s, and CA50 steel is the most currently employed as reinforcement of concrete structures. Besides the type of steel, the study evaluated the influence of bar diameter (5mm and 25mm ) in the process of passivation, depassivation and propagation of corrosion. For the study, steel bars 5mm and 25mm, of the CA24 and CA50 were introduced in body-of-proof molded prismatic with a reference concrete. The bodies of the specimen underwent regular cycles of immersion in NaCl solution with 2 % concentration and drying. Were also shaped bodies-specimens with 3% sodium chloride in the mixing water by mass of cement. These remained initially in place with controlled humidity 55 ± 15 % and subsequently passed through cycles of immersion in clean water and drying. Monitoring for 210 days, the corrosion was evaluated by the electrochemical corrosion potential measurements (Ecorr) and polarization resistance (icorr). The concrete was monitored by measurements of surface resistivity (ρ). Before corrosion valuation, metallographic tests, chemical composition and mechanical tests for steel characterization were performed. The electrochemical mass loss were compared with the gravimetric weight loss, showing that steel CA50 to CA24 in comparison, is more susceptible to corrosion. The study also showed that steels with smaller diameter have lower corrosion resistance.